An observational study of early neonatal outcome in babies born to mothers with pregnancy induced hypertension - C., Ramya; Kumari, Rathna; Chitneni, Charishma (International Journal of Contemporary Pediatrics, 2020)
Background: Hypertensive disorders in pregnancy are a major cause of maternal morbidity and mortality accounting for 15-20% of maternal deaths worldwide. In India the incidence of preeclampsia is reported to be 8-10 percent of the pregnancies objective of this study was to with the above background, this study was carried out to study early neonatal outcome in babies born to PIH mothers, Measure the adverse neonatal outcomes in the early neonatal period and compare the mode of delivery between control group and PIH group. Methods: A total of 58 neonates born to mothers diagnosed having gestational hypertension, preeclampsia, eclampsia were taken as tests (group A), and 100 apparently healthy newborns born to normotensive mothers were enrolled as controls (group B) and followed up to 1st week of life. The outcome measures were compared between groups in terms of mode of delivery, preterm delivery, birth weight, APGAR score, intra uterine growth retardation, early neonatal complications. Results: In group A, 33 had LBW (56.89%) and in group B 18 had LBW (18%). The incidence of preterm deliveries in group A was higher as compared to group B (A- 43.10%, B-17%, p value <0.05). Babies born to PIH mothers had an increased incidence of IUGR, as compared to group B. Conclusions: PIH is one of the major causes of maternal, fetal and early neonatal morbidity and mortality. In this study authors found that risk of LBW, preterm delivery, NICU admission and IUGR in babies born to PIH mothers statistically significant. Early detection of high-risk individual by well trained personnel and timely referral to advanced tertiary center is necessary in bringing down the maternal and neonatal morbidity and mortality.